ҚАРАҚАЛПАҚ ӘДЕБИЯТТАНЫЎ ИЛИМИНДЕ ЛИРИКАЛЫҚ ОБЪЕКТ МӘСЕЛЕСИ - Дабылов, П. (FAN va JAMIYAT, 2023)
This article discusses the scientific views and opinions expressed by Karakalpak scientists on the issue of the lyrical object, which is not the object of a special study in Karakalpak literature. The place and role of the lyrical object in creating the image of the lyrical hero are shown. The specific features are revealed of in the lyrical object. As a result, the question of the lyrical object is argued from a scientific point of view.